SEED BURIAL EXPERIMENT FOR ALPINE PLANTS - R. K. Adzhiev; V. G. Onipchenko (Юг России: экология, развитие)
They Are Analysed material of the examination influence of the people surplus moistening and flooding landscape Stavropoliskiy edge.